Margosatubig the story of Salagunting - Muzones, Ramon L. (Ateneo de Manila University Press, 2012)
"Ramon L. Muzones claims his rightful place in the national literature of the Philippines with Cecilia Locsin-Nava's English translation of Margosatubig, a Hiligaynon novel that was to re-write the history of the West Visayan fiction when it first appeared as a serial novel in 1946 in the pages of the popular magazine Yuhum. Muzones tells the story of a fictive Muslim state in Mindanao that loses its legitimate rulers through intrigue and treachery and how the hero-heir Salagunting leads the struggle to recover Margosatubig from the usurpers. Muzones shows himself a master of narrative invention in 30 installments that unfold a wealth of precolonial lore that blended romance, adventure, fantasy, subtle eroticism, and geographic information that so fascinated magazine readers and made Yuhum's weekly circulation jump from 2,500 to 37,000."--Back Cover.